Application of Self-Healing Intelligent Polymer Materials in Anti-aging Research. (September 2020) - Huo, Lianyi; Allman, Alan; Chen, Siming
Abstract: The self-healing materials come from the bionic research of the self-healing phenomenon of the organism. Self-healing materials can self-repair and restore some mechanical properties when damaged. With the development of material science in recent years, more and more attention has been paid to intellectual materials. Self-healing polymer materials play an important role in the field of intellectual materials because of their unique properties. It is significant for polymer materials in the engineering field to repair micro-cracks in time. This article summarizes the related characteristics of self-healing polymer intellectual materials and the causes and coping modes leading to the aging of polymer materials, as well as the application of self-repairing polymer intelligent materials at home and abroad in anti-aging research, and expounds its broad prospects for development.